ADAPTOGENIC EFFECTS OF PANAX GINSENG PLANT EXTRACT ON IMMUNE MODULATION IN LAYERS AGAINST SALMONELLA ENTERITIDIS - TAIMOOR, M; NOOR, H; YASMIN, S; USMAN, M; ASHRAF, D; HUSSAIN, D; IQBAL, S; HASAN, W; ZAFAR, N; AJAZ, R (Biological and Clinical Sciences Research Journal, 2024)
Panax ginseng, a traditional medicinal herb known for its adaptogenic properties, has garnered significant attention for its potential role in immune modulation and disease prevention. In this study, we investigate the adaptogenic effects of Panax ginseng on immune modulation in layers against Salmonella Enteritidis. This randomized control trial was conducted at the University of Agriculture, Faisalabad, from January 2023 to October 2023. A total of 450 laying hens were included in this study. The laying hens were randomly assigned to different experimental groups to ensure unbiased representation and minimize confounding variables. The laying hens were separated into several experimental groups, including a benchmark group and one or more treatment groups receiving Panax ginseng supplementation. A total of 450 laying hens were included in the study, divided into five experimental groups: a control group (n = 90) and four treatment groups receiving varying doses of Panax ginseng supplementation (n = 90 each). Compared to the control group, hens receiving low, medium, and high portions of ginseng displayed elevated degrees of IgG and IgM antibodies. Specifically, the high-portion ginseng group demonstrated the most noteworthy mean values for both IgG (75 ± 18) and IgM (50 ± 12), indicating a vigorous invulnerable reaction. It is concluded that supplementation with Panax ginseng holds promise as a natural intervention for enhancing immune modulation and reducing pathogen load in laying hens challenged with Salmonella Enteritidis. Ginseng may serve as a valuable adjunct therapy in poultry production to mitigate infectious diseases and improve overall health outcomes.